Penerapan Metode Speed Reading Untuk Meningkatkan Hasil Belajar Siswa Kelas V pada Mata Pelajaran Bahasa Indonesia SD Negeri 11 Watampone Kecamatan Tanete Riattang Kabupaten Bone - Abd. Kadir. A; Asriadi Asriadi; Nur Asmira Asman (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2023)
The problem of this research is the low learning outcomes of students in Indonesian subjects. The formulation of the problem in this study is how to apply the Speed Reading Method to improve the learning outcomes of fifth grade students in Indonesian language subjects at SD Negeri 11 Watampone, Tanete Riattang District, Bone Regency? The purpose of this study was to describe the application of the Speed Reading method to improve the learning outcomes of fifth grade students in Indonesian subjects at SD Negeri 11 Watampone, Tanete Riattang District, Bone Regency. The approach in this study is a descriptive qualitative approach. This type of research is CAR recycling. The focus in this research is 1) Application of Speed Reading method, 2) Student learning outcomes. The subjects in the study were fifth grade students at SD Negeri 11 Watampone, Bone Regency. The subjects in this study were 25 students consisting of 12 boys and 13 girls. Data collection techniques used are observation, tests and documentation. Data analysis techniques in this study are data reduction, data presentation and drawing conclusions. The results of the study showed an increase. Cycle I achieved the qualification of Good (B) and in the second cycle achieved the qualification of Very Good (A). The conclusion of this study is that applying the Speed Reading method can improve student learning outcomes in Indonesian subjects in Class V SD Negeri 11 Watampone, Tanete Riattang District, Bone Regency.